Interior RC wide beam-narrow column joints: Potential for improving seismic resistance. (15th September 2015) - Elsouri, A.M.; Harajli, M.H.
Highlights: Gravity load-designed interior wide and shallow beam-column joints (as-built) cannot be considered as earthquake-resistant. It is possible to improve the seismic behavior of the subject joints by improving their steel detailing without imposing significant changes in their design and construction practices. The joints with improved steel detailing performed much better under cyclic loading than the as-built joints by developing large lateral load, drift and energy dissipation capacities. Abstract: Design codes (ACI 318-08, 2008; ACI Committee 352-02, 2010) place restrictions on the use of reinforced concrete (RC) wide-beam framing systems in regions of seismic hazard because there are little or insufficient information about their behavior under the effects of earthquake loads. The current study constitutes the second part of an experimental investigation carried out for (i) evaluating the seismic response of RC wide and shallow beam-narrow column joints when designed and detailed under gravity load; and (ii) for exploring the potential of improving the seismic performance of the same joints without introducing significant changes in the design and construction practices. The first part of the investigation concentrated on exterior joints, the results of which were reported elsewhere (Elsouri, 2013). This study concentrates on interior joints, in which four full-scale beam-column sub-assemblages were tested under quasi-static cyclic loading. Two of the joints, referred to as "as-built", were designed and detailed for gravity load in accordance with local design and construction practices. The other two joints, referred to as "earthquake-resistant", were also designed assuming gravity load but their reinforcement detailing were improved to satisfy part of the ACI 318-08 requirements and ACI-ASCE 352-02 recommendations for seismic-resistant structures. The as-built joints experienced shear failure within the joint core at early lateral drift. With a slight improvement of the reinforcement detailing, despite violating the limits of joint dimensions and some detailing requirements of ACI 318-08, the earthquake-resistant joints acquired considerably improved seismic performance by preventing or delaying joint shear failure; and by developing higher lateral load, deformation, and energy dissipation capacities when compared with the as-built joints.